A novel ultrasonic intraocular lens (IOL) cutting tip and IOL holding forcep - Neha Dholakia; Onkar H Pirdankar; Smitesh Shah (Indian Journal of Ophthalmology, 2025)
To address the challenges related to IOL explantation and associated complications, we have developed an innovative tip that utilizes the ultrasonic power of phaco machine for efficient IOL cutting. The tip can be easily screws into phaco machine, while the other end is forked with sharp inner margins. This cutter is complemented by the ergonomically designed microforceps which are inserted through a side port to grasp the lens securely during cutting.